The engineer. professional and citizens (Revista Electrónica REDINE, 2018)
This article is presented as a reflection of the learning process engineer, but not only professionally prepared within the technical area, but also as a citizen, as an active social actor in their environment and civic competences on this. As teachers not only have the function of preparing future professionals who will graduate from each of the houses of studies where we work, but we must also educate citizens, social actors with their knowledge and their contributions improve our society. Through education and citizenship values ​​will be achieved rescue the identity of persons and deteriorated and despondent society in which we live.
Keywords: teacher; engineer; citizen; social actor